Water Deficit Severity during the Preceding Year Determines Plant Tolerance to Subsequent Year Drought Stress Challenges: A Case Study in Damask Rose - Fatemeh Aalam; Abdolhossein Rezaei Nejad; Sadegh Mousavi-Fard; Mohammadreza Raji; Nikolaos Nikoloudakis; Eleni Goumenaki; Dimitrios Fanourakis (Horticulturae, 2024)
Damask rose is an important essential oil crop. In the present study, plants were subjected to three different water deficit levels (70, 40, and 10% available water content) for two periods (June–October). Plant phenology, growth, essential oil yield, gas exchange features, membrane stability and major antioxidant defense elements were monitored across two years. Soil water deficit was related to quicker completion of the growth cycle (up to 7.4 d), and smaller plants (up to 49.7%). Under these conditions, biomass accumulation was jointly constrained by decreased leaf area, chlorophyll content, CO2 intake, and photosynthetic efficiency (up to 82.8, 56.9, 27.3 and 68.2%, respectively). The decrease in CO2 intake was driven by a reduction in stomatal conductance (up to 41.2%), while the decrease in leaf area was mediated by reductions in both number of leaves, and individual leaf area (up to 54.3, and 64.0%, respectively). Although the reactive oxygen species scavenging system was activated (i.e., proline accumulation, and enhanced activity of three antioxidant enzymes) by water deficit, oxidative stress symptoms were still apparent. These effects were amplified, as soil water deficit became more intense. Notably, the adverse effects of water deficit were generally less pronounced when plants had been exposed to water severity during the preceding year. Therefore, exposure to water deficit elicited plant tolerance to future exposure. This phenotypic response was further dependent on the water deficit level. At more intense soil water deficit across the preceding year, plants were less vulnerable to water deficit during the subsequent one. Therefore, our results reveal a direct link between water deficit severity and plant tolerance to future water stress challenges, providing for the first time evidence for stress memory in damask rose.